Effect of fluctuation of water level on stability of dike - Salim, Sutomo. (2013)
The increasing demand of dike construction from the past as prevention measure against land inundation to the current context for land reclamation project to meet the needs of increasing population has required attention to ensure the performance and safety of the dike as it protects many lives and great economic value. For the latter usage, sea water level will be higher than the water level inside the land imposing seepage flow through dike body that would affect the stability. In addition, water level is not constant, it fluctuates with time. Limitation of past studies not accommodating such two aspects has brought up this study. This paper presents a study to examine the effect of fluctuation of water level on stability of dike by conducting simulation study using finite-element analysis softwares, Plaxis and GeoStudio. Both softwares analyse flow using finite-element method. The difference is on the method calculating slope factor of safety, the first uses finite-element method and the latter uses limit equilibrium method. A total of 8 pairs of models, 8 models each for respective software with varying tide amplitudes, tide periods, and dike heights were evaluated to examine the performance of dike.